Analysis Of Employee Reward and Punishment at CV. Bestro Project Sumedang - Amanda, Helles; Nurzaman, Aditya; Karmila, Ila; Supriatna, Jajang; Wulansari, Devie (Journal of Bussines Management Basic, 2025)
Bestro Project Sumedang is a company engaged in the convection and printing industry. This study aims to find out how the implementation of reward and punishment for employees at CV. Bestro Project Sumedang. This study used a qualitative research method with reward and punishment variables. The sampling technique used purposive sampling technique. The research informants consisted of 5 people, namely Owner/Director, Manager, Head of Production, DTF Operator and Marketing. Data analysis using the Miles and Huberman model includes data collection, data reduction, data presentation, and drawing conclusions. The results showed that the implementation of rewards at the company was good, including salaries given in accordance with company policies, bonuses given according to employee performance, appreciation in the form of praise for performance achieved and fostering a family system within the company. While the punishment that is implemented is still not optimal. Thepunishment applied is light punishment in the form of verbal and written warnings, moderate punishment in the form of a decrease in salary and severe punishment in the form of termination of employment. CV. The Bestro Project is expected to be able to apply rewards and punishments fairly so that employee performance increases.